Perancangan Sistem Informasi Penjualan Dengan Pendekatan Metode Waterfall - Wati Erawati (STMIK Budi Darma, 2019)
Along with the rapid development of science and technology, the need for fast and accurate information is needed by every company. To manage information requires good and sophisticated technology. The technology needed is not only in the form of hardware (Hardware) and also in the form of software (Software), but has great value for those who use it. One of the support to make it happen is to process company data using a computerized system. In this research method, the method used is the waterfall method as a pattern of system development. until now has not been computerized, while the information system is very supportive and provides satisfying services for customers. For this reason the author discusses the design of a sales information system at the Sono Snack Shop with a program that facilitates the shop. The design of this information system is the best solution to solve the problems that exist in this store, and with a computerized system can be achieved an activity that is effective and efficient in supporting the activities of this store.